Efek penyuluhan metode demonstrasi menyikat gigi terhadap penurunan indeks plak gigi pada murid sekolah dasar Effect of demonstration method counseling on brushing teeth to the decreasing of plaque value of elementary school students - Muhammad Ilyas; Indah Nisita Putri (Journal of Dentomaxillofacial Science, 2012)
Dental and oral health education to primary school children is one of the efforts to improve the health of the teeth inchildren for the preventive and promotive aspects. The choice of demonstration method on dental and oral healtheducation to support increasing understanding of the child, with doing practice the correct way to brush teeth. Thepurpose of this study was to compare the effectiveness of oral health education to decrease plaque index at sixth gradeelementary school students. This research is a quasi-field experimental design with pre and posttest with control group.Subjects consisted of all sixth grade students in the village Padang Loang, District Patampanua, Pinrang. With clusterrandom sampling got 49 students. Data were analyzed using t-test. The results showed that one week after illuminationwas applied value of plaque decline 2.269 at the treatment group. While the control group have increasing value ofplaque 0.485. The data indicate that there are effects of oral and dental health education demonstration method insixth grade elementary school students. It was concluded that the introduction of the importance of oral health as ahealth maintenance efforts should be done from an early ages, it needs good cooperation between students, teachersand parents.